Dentists' Knowledge and Clinical Experience towards Molar-Incisor-Hypomineralization in Iran - Fatemeh Sadat Sajadi; Naimeh Hasheminejad; Alireza Mehdizadeh; Ali Eskandarizadeh; Mohammadreza Rostamizadeh (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine the knowledge and clinical experience of dentists regarding MIH in Kerman/Iran. Material and Methods: In this cross-sectional study, a census sampling method was used, and all dentists registered in Kerman medical council were asked to participate in the study. A validated and reliable researcher administered questionnaire was used to determine participants' demographic characteristics, knowledge, and clinical experience. The association between knowledge score and demographic variables was determined using an independent t-test and ANOVA. The level of significance was set as 0.05. Results: Overall, 400 specialized and general dentists in Kerman completed the questionnaire. The mean knowledge score of dentists was 6.6±1.9 of 11. Female dentists' knowledge was higher than male dentists (p<0.05). General dentists had a higher level of knowledge regarding MIH compared to specialists (p<0.05). Overall, 79.5 % had been faced with MIH during their practice years. After confronting MIH teeth, 48.8% of dentists referred patients to specialists for treatment. Providing aesthetics was considered the most difficult part of treatment (43.2%). Resin composite was the most favorable dental material for treating MIH (60.9%). Conclusion: Although most dentists in Kerman had encountered MIH defects during their clinical practice, they did not have enough knowledge of the defect and required education on all aspects of MIH diagnosis and management. Younger dental practitioners, general dentists and females presented higher knowledge of MIH.